Investigating Friction and Antiwear Characteristics of Organic and Synthetic Oils Using h-BN Nanoparticle Additives: A Tribological Study - Umida Ziyamukhamedova; Shah Wasil; Sanjay Kumar; Rakesh Sehgal; M. F. Wani; Chandra Shekhar Singh; Nodirjon Tursunov; Himanshu Shekhar Gupta (Lubricants, 2024)
Friction and wear are two major elements that influence the life of a variety of equipment. According to estimates, as much as 30% of the energy used is dissipated as friction. However, this figure can be reduced by developing materials that enhance surfaces and apply lubricants appropriately. This study aims to analyze the impact of hexagonal boron nitride (h-BN) nanoparticles on the rheological and antiwear characteristics of four distinct oil varieties, namely Society of Automotive Engineers SAE-20W50, soybean, Polyalphaolefin PAO-4, and olive oils. The results of the tribological tests demonstrated a noteworthy enhancement in antiwear characteristics with the addition of 0.2 wt.% of h-BN nanolubricant. Among all nanolubricants, the maximum reduction in coefficient of friction (COF) and wear scar diameter was observed at 0.2 wt.% of h-BN in SAE-20W50 oil. Compared to the base oils, the wear scar diameter decreased by 17.93%, 8.80%, 22.65%, and 24.04% for (soybean oil and 0.2 wt.% of h-BN), (SAE20W50 and 0.2 wt.% of h-BN), (PAO4 and 0.2 wt.% of h-BN), and (olive oil and 0.2 wt.% of h-BN), respectively. Rheological test results indicated that with the addition of h-BN nanoparticles, the viscosity of the base oils significantly increased. The maximum viscosity was observed at 40 °C for SAE20W50 base nanolubricants, according to the rheological measurements.